Relationships between pathologic subjective halitosis, olfactory reference syndrome, and social anxiety in young Japanese women - Tsuruta, M.; Takahashi, T.; Tokunaga, M.; Iwasaki, M.; Kataoka, S.; Kakuta, S.; Soh, I.; Awano, S.; Hirata, H.; Kagawa, Masaharu; Ansai, T. (2017)
Background: Pathologic subjective halitosis is known as a halitosis complaint without objective confirmation of halitosis by others or by halitometer measurements; it has been reported to be associated with social anxiety disorder. Olfactory reference syndrome is a preoccupation with the false belief that one emits a foul and offensive body odor. Generally, patients with olfactory reference syndrome are concerned with multiple body parts. However, the mouth is known to be the most common source of body odor for those with olfactory reference syndrome, which could imply that the two conditions share similar features. Therefore, we investigated potential causal relationships among pathologic subjective halitosis, olfactory reference syndrome, social anxiety, and preoccupations with body part odors. Methods: A total of 1360 female students (mean age 19.6 ± 1.1 years) answered a self-administered questionnaire regarding pathologic subjective halitosis, olfactory reference syndrome, social anxiety, and preoccupation with odors of body parts such as mouth, body, armpits, and feet. The scale for pathologic subjective halitosis followed that developed by Tsunoda et al.; participants were divided into three groups based on their scores (i.e., levels of pathologic subjective halitosis). A Bayesian network was used to analyze causal relationships between pathologic subjective halitosis, olfactory reference syndrome, social anxiety, and preoccupations with body part odors. Results: We found statistically significant differences in the results for olfactory reference syndrome and social anxiety among the various levels of pathologic subjective halitosis (P < 0.001). Residual analyses indicated that students with severe levels of pathologic subjective halitosis showed greater preoccupations with mouth and body odors (P < 0.05). Bayesian network analysis showed that social anxiety directly influenced pathologic subjective halitosis and olfactory reference syndrome. Preoccupations with mouth and body odors also influenced pathologic subjective halitosis. Conclusions: Social anxiety may be a causal factor of pathologic subjective halitosis and olfactory reference syndrome.